Impact of Advertising Appeals on Brand Loyalty; with Special Reference Milk Powder Industry in Sri Lanka - Dilshan, M. G. A. A.; Weerasiri, R. A. S. (Department of Marketing Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka., 2025)
This study was conducted to identify the impact of Advertisement appeals on brand loyalty the Milk powder industry in Sri Lanka. The research shows how advertisement appeals emphasize brand loyalty within the sector. There are numerous advertisements developed for the milk powder sector. In this research, the researchers want to investigate the secret behind it. Primarily, the researchers wanted to explore what the best advertising appeals are for cultivating brand loyalty. The study emphasizes the role of emotional branding, advertising strategies, and consumer engagement in fostering long-term brand loyalty. Recognizing the importance of the milk powder industry as a critical component of the Sri Lankan market, the research aims to bridge identified empirical and practical gaps by examining the relationship between advertising appeals and consumer attachment to brands. The quantitative approach is most appropriate for this study, as it involves both the collection and the analysis of numerical data, thus facilitating an objective examination of the relationship among key variables. A structured questionnaire created especially to examine factors pertaining to emotional, Rational and moral advertising appeals and their impact on brand loyalty is used to gather the main data for this study. By ensuring that standardized data is collected, this approach makes it possible to compare and analyze responses consistently. Primary data was collected from 412 respondents, with 403 valid responses we reanalyzed using statistical tools such as SPSS. The findings confirm that experiential Emotional appeals and moral appeals positively impact brand loyalty and Rational appeals negatively impact brand loyalty. When consumers feel a brand resonates with their values or experiences, they are more likely to remain loyal. For example, a milk powder brand emphasizing a nurturing mother's love or a child's happiness can foster an emotional attachment, encouraging repeat purchases. The results show that by creating strong emotional bonds and favorable customer associations, emotional appeals and moral message advertisements significantly enhance brand loyalty. For marketers and other industry experts looking to create successful advertising campaigns that connect with Sri Lankan customers and increase brand loyalty and long-term customer retention, the research provides insightful information. The study faces limitations including cultural diversity, challenges in isolating advertising impacts, restricted data access, cultural specificity limiting global applicability, and time constraints restricting comprehensive data collection from all Sri Lankan regions. The implications of this research highlight the importance of leveraging emotional branding and neuromarketing strategies to build deep connections with Sri Lankan consumers through ads that evoke nostalgia, humor, and happiness while incorporating emotional storytelling with family and child-centric themes additionally, emphasizing ethical messaging such as eco-friendly packaging and community support fosters loyalty and trust.
Keywords: Advertisement appeals; Brand loyalty; Emotional appeals; Moral appeals; Rational appeals